Revealing the Interaction Between Dislocations and LPSO-Precipitates Structure in a Mg-Y-Al Alloy at Different Temperatures - Qingchun Zhu; Yangxin Li; Huan Zhang; Jie Wang; Hongxiang Jiang; Jiuzhou Zhao (Crystals)
Precipitation strengthening represents a crucial strengthening approach in the realm of metals, with particular significance for magnesium. In this study, a complex LPSO–precipitate structure, which is constituted of the principal secondary phases in Mg rare earth (RE) alloys, namely the Long-Period Stacking Ordered (LPSO) phase and the aging precipitate, was successfully fabricated within a Mg-11Y-1Al alloy. Subsequently, an in-depth investigation was conducted regarding the interaction between dislocations and this LPSO–precipitate structure under varying temperature conditions. The findings revealed that, at room temperature (RT), the aging precipitates effectively hindered the movement of basal dislocations, and the activation of non-basal dislocations is rather difficult, resulting in the alloy’s high strength and low plasticity. When the temperature was elevated to 200 °C, although non-basal slip could be initiated, the LPSO–precipitate structure was capable of blocking both basal and non-basal slips. Consequently, the alloy still demonstrated high strength and low plasticity. As the temperature further increased to 250 °C, dislocations could cut through the aging precipitate particles, and the interior of the grains could provide partial deformation. Hence, the tensile elongation of the alloy was significantly enhanced, increasing from 4% to 12% as the temperature was elevated from 200 °C to 250 °C. These results suggest that the LPSO–precipitate structure still exerts a remarkable strengthening effect at 200 °C. When the temperature reaches 250 °C, the plasticity of the alloy is improved but its strength decreases. The research outcomes presented in this paper offer a novel perspective for the precise tailoring of mechanical properties through precipitation strengthening within Mg-RE alloys.